A distinctive new species of the genus Thrips Linnaeus (Thysanoptera, Thripidae) from Saudi Arabia and a revised key to the Arabian Peninsula species - Rasool, Iftekhar; Ansi, Amin N. Al; Aldhafer, Hathal M. (Zootaxa, 2025)
Thrips jazanensis sp. nov. is described based on both sexes collected on the flowers of parasitic plants Araujia sp. and Pergularia sp. (Apocynaceae). The relationship among some closely related species and their host plants is discussed. Two species, T. microchaetus and T. subnudula are recorded for the first time from Saudi Arabia. A key to the twelve Arabian Peninsula species of genus Thrips is also given.